Baicalin Alleviates LPS-Induced Oxidative Stress via NF-κB and Nrf2–HO1 Signaling Pathways in IPEC-J2 Cells - Bao, Minglong; Liang, Mei; Sun, Xinyi; Mohyuddin, Sahar Ghulam; Chen, Shengwei; Wen, Jiaying; Yong, Yanhong; Ma, Xingbin; Yu, Zhichao; Ju, Xianghong; Liu, Xiaoxi (Frontiers in Veterinary Science, 2022)
Baicalin is a natural plant extract with anti-inflammatory and anti-oxidant activities. However, the molecular mechanism of baicalin on oxidative stress in IPEC-J2 cells exposed to LPS remain unclear. In this study, LPS stimulation significantly increased Toll-like receptor 4, tumor necrosis factor-α, and interleukins (IL-6 and IL-1β) expression in IPEC-J2 cells, and it activated the nuclear factor (NF-κB) expression. While, baicalin exerted anti-inflammatory effects by inhibiting NF-κB signaling pathway. LPS stimulation significantly increased the levels of the oxidative stress marker MDA, inhibited the anti-oxidant enzymes catalase and superoxide dismutase, which were all reversed by baicalin pre-treatment. It was found that baicalin treatment activated the nuclear import of nuclear factor-erythroid 2 related factor 2 (Nrf2) protein, and significantly increased the mRNA and protein expression of its downstream anti-oxidant factors such as heme oxygenase-1 and quinone oxidoreductase-1, which suggested that baicalin exerted anti-oxidant effects by activating the Nrf2-HO1 signaling pathway. Thus, pretreatment with baicalin inhibited LPS - induced oxidative stress and protected the normal physiological function of IPEC-J2 cells via NF-κB and Nrf2–HO1 signaling pathways.